New oligomeric metallosiloxane - polyimide nanocomposites for anti-atomic-oxygen erosion. (January 2021) - Andropova, Ulyana; Serenko, Olga; Tebeneva, Nadezhda; Tarasenkov, Aleksander; Askadskii, Andrey; Afanasyev, Egor; Novikov, Lev; Chernik, Vladimir; Voronina, Ekaterina; Muzafarov, Aziz
Highlights: In situ filling of polyimide (PI) promotes an increase of its glass transition temperature. PI with metallosiloxane-based particles is promising protective coating for spacecrafts. The precursor structure determines the AO erosion resistance of polymer nanocomposite. Specific erosion yields identify key factors determining protective coating properties. Abstract: The effect of branched functional metallosiloxane oligomers (BFMSO) used as precursors on the morphology and atomic oxygen resistance of filled polyimide films was studied. Nanocomposites are characterized by elevated glass transition temperatures and greater erosion resistance to atomic oxygen than the original polymer. In situ filling of polyimide with BFMSO-based nanoparticles allows one to reduce the rate of film mass loss under the influence of atomic oxygen by an order of magnitude and reduce the erosion yield by more than 70%. To correctly compare the effectiveness of fillers based on precursors of different chemical structures as protective elements of the polymer surface from the effects of atomic oxygen, the specific erosion yields calculated as the ratio of the erosion yield to the filler concentration expressed in moles of filler per unit mass of polymer were used. This approach made it possible to identify the main factors of the directional regulation of erosion resistance of in situ filled PI to the effects of atomic oxygen. Primarily they include the chemical structure of the organic frame of the central metal atom of the precursor, which determines the effectiveness of the filler in increasing the erosion resistance of nanocomposites. The "replacement" of a phenyl substituent with a methyl substituent at a silicon atom in the composition of BFMSO and, accordingly, particles based on it, reduces the specific erosion yields of nanocomposites by 2.2-2.6 times. The nature of the central metal atom of the precursor is a minor factor. Its change allows reducing the specific erosion yields of coatings based on polyimide and branched functional metallosiloxane oligomers by no more than 1.5 times.